The Relationship Between Community Participation In Tourism Development And The Quality Of Life Of The Community In Bintan Regency - Ferizone, Ferizone; Siam, Nurbaiti Usman; Sanopaka, Endri (Universitas Riau Kepulauan, 2025)
Quality of life of the community is an important indicator of well-being. The aim of this study is to examine the relationship between community participation in tourism development and community quality of life in framework of economi cooperation area. Importance of this research is to find out whether the government's efforts to improve the quality of life of the community through tourism have had an impact on the quality of life of the community. This study involved a sample of 354 respondents. The samples were taken from 10 districts within Bintan Regency using multistage random sampling, and data collection was conducted through systematic random sampling methods.After conducting the validity and reliability tests, the results indicated that the research instrument is both valid and reliable. Subsequently, a correlation test was performed using the Pearson Correlation method, which yielded an r-square value of 0.283. The result that show community participation in tourism development has a weak yet positive relationship with the quality of life of the community. The positive relationship indicates that the higher the level of community participation in tourism, the better their quality of life is likely to improve. Based on these results, the conclusion that can be drawn from this study is that the government's efforts to improve the community's economy based on tourism have not been successful even though there is an economic cooperation framework in the Bintan Regency area.